By the light of the moon - Koontz, Dean R. (Dean Ray), 1945- (New York : Bantam Books, 2002)
After Dylan O'Connor, a gifted young artist, and Jillian Jackson, a struggling comedian, are injected with a strange substance, they embark on a twenty-four hour odyssey of terror, mystery, and discovery.
Accelerated Reader AR
Keywords: Artists -- Fiction; Psychics -- Fiction; Brothers -- Fiction; Women comedians -- Fiction; Autistic people -- Fiction; Suspense fiction